HEDONIC TEST AND HEDONIC QUALITY TEST OF KOMBUCHA FROM VARIOUS TYPES OF INDONESIAN HERBS - Nisak, Yunita Khilyatun; Khurniyati, Maylina Ilhami; Nurbaya, Syarifa Ramadhani; Nugroho, Endik Deni (Jurnal IPTEK, 2023)
Since the COVID-19 pandemic, people have learned the importance of consuming vitamins or supplements that boost the immune system. In fact, compounds that enhance the immune system, usually called immunomodulators, can be obtained easily around us, one of which is from TOGA (Family Medicinal Plants). Even though TOGA has been known for a long time, the utilization of TOGA still needs to be improved, even though the bioactive compounds in TOGA can be utilized, one of which is by fermenting it into kombucha. The method used in this study is quantitative and descriptive. The results of this study indicate that based on pH analysis, kombucha had a pH between 3.4 and 3.89 before fermentation. Meanwhile, after fermentation, the kombucha pH dropped to 2.89 – 3.08. The results of the hedonic test showed that curcuma kombucha had the highest average value in terms of aroma, colour, flavour, sensation of soda and overall preference. The results of the hedonic quality test showed that the preferred TOGA kombucha had a slightly pungent aroma, pale yellow colour, quite sour flavour and quite pronounced soda sensation.